Pengaruh Kebijakan Dividen, Likuiditas dan Solvabilitas terhadap Harga Saham Perusahaan Manufaktur Sub Sektor Barang Konsumsi yang Terdaftar di BEI - Manik, Nadia Putri; Aulia, Aulia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Stock prices on the stock exchange are not always stable, sometimes rising and sometimes falling, depending on the strength of demand and supply. Therefore, this study was carried out in order to determine the influence of dividend policies, liquidity and solvency on the stock prices of manufacturing companies in the consumer goods sub-sector that are verified on the IDX. This study uses a quantitative approach using statistical analysis of panel data regression. The population studied is 47 manufacturing companies in the Consumer Goods Sub-Sector. The sample in this study is 20 companies. The period that will be used from 2019 - 2022 is 4 years. Thus, the number of N in this study is 20 x 4 = 80. The data analysis technique uses multiple linear regression. The results of his research show that dividend policy is measured by DPR, liquidity is measured by CR, solvency is measured by DAR has an effect on stock prices measured by PBV.